Impact of Secure Messaging Telehealth Service on the Quality of Health Care - Ko, PhD, Dong-Gil (Telehealth and medicine today, 2023)
Importance: Secure messaging is the only rapidly growing virtual care in the telehealth ecosystem; it is a cost-effective way to get medical advice and an alternative to an in-person, video, or telephone visit. Secure messaging has been shown to positively affect patients manage chronic diseases, improve health awareness and literacy, and improve communication and care coordination. However, providers have seen a 200% increase in secure messages in the past few years with some that are associated with medical visit avoidance and providers’ burnout. Such paradoxical tension raises questions about the value of secure messages and whether it impacts the quality of health care outcomes. Objective: Conduct an empirical assessment and evaluate the extent to which and for whom secure messages improve the quality of health care. Methods: Electronic health records of adult patients with type 2 diabetes mellitus with an active patient portal account who visited the Academic Medical Center between 2015-2020 were included in the analysis. Patients must have also initiated a secure message, made a follow-up in-person appointment, and completed the CAHPS (Consumer Assessment of Healthcare Providers and Systems) patient satisfaction survey. Results: The final regression analysis included 1,332 patients with no missing data. The results reveal a negative relationship between patients who discuss their secure messages during their encounters and patient satisfaction even after controlling for patient-specific (age, gender, insurance), provider-specific (responsiveness), and medical conditions (average blood sugar, mean arterial pressure). The results also show a stronger negative effect for the underrepresented minorities (Blacks and Hispanics). Discussion: The negative relationship between secure message exchanges and patient satisfaction may stem from different mental models between patients and providers as stocks of prior knowledge. Providers with their subject matter expertise have mental models that are incongruent with patients’ general health knowledge suggesting that the patients may struggle to recognize the value of new information, assimilate it, and apply it. On the other hand, effective communication is fundamental to patient satisfaction, and providers may be challenged to instill greater understanding during their average 18-minute encounters. The proliferation of digital divide research in health care indicates that Blacks and Hispanics are at a disadvantage; therefore, it is not unreasonable to suggests that the rate of health literacy differs possibly creating greater uncertainty and ambiguity. More research is needed that probes into the role and value of secure messaging as health care providers begin to charge patients for this telehealth service.